Isolation and identification of Helicobacter pylori from raw chicken meat in Dhamar Governorate, Yemen - Almashhadany, Dhary Alewy; Mayas, Sara Mohammed; Ali, Noor Lutphy (Italian Journal of Food Safety, 2022)
Although Helicobacter pylori (H. pylori) is one of the most common bacterial pathogens of human, its natural reservoirs are still unclear. There is an increasing number of reports that document the occurrence of H. pylori in various foods. This study aimed at isolation of H. pylori from chicken meat sampled. Two hundred and sixty samples were collected randomly from slaughterhouses and markets in Dhamar Governorate, Yemen. Samples were enriched in Brain-Heart Infusion broth in microaerophilic conditions before inoculating the Camp-Blood agar and EYE agar plates. Results showed that 13.8% of samples were contaminated evidenced by H. pylori growth via traditional culture method on agar media. No significant differences between sample types (thighs and breast muscles) (p=0.353) or the sampling source (p=0.816) were observed. Autumn season was associated with increased occurrence of H. pylori. The source of H. pylori in food is still not identified. Proper cooking and good sanitation practices are highly recommended to avoid the infection. Further studies addressing the potential sources of H. pylori are highly suggested.